Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO) in Diverse Ethnic Groups. Issue 4 (18th June 2013) - Roggman, Lori A.; Cook, Gina A.; Innocenti, Mark S.; Jump Norman, Vonda; Christiansen, Katie
ABSTRACT Parenting interactions are important for children's early development, but existing observational measures of parenting are often difficult for practitioners to use in their work with parents and have been developed based on primarily European American middle‐income parents. Practitioners working with parents of infants and young children need a psychometrically strong observational measure of parenting behaviors appropriate for diverse groups. We tested the reliability and validity of 89 specific parenting behavior items by having observers rate over 4, 500 viderecorded observations of parent–infant interaction from the archive of the Early Head Start Research and Evaluation Project and other research. These observations at multiple age points were from over 2, 000 low‐icome families, including European Americans, African Americans, and Latino Americans. Interrater agreement was tested for each item. Scale internal consistency and single‐factor structure were tested within each of four domains—affection, responsiveness, encouragement, and teaching. Validity was tested with concurrent parenting measures and child development outcome measures. The 29 most consistently reliable and valid items comprise the final version of Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO), an evidence‐based observational measure of parenting with very young children that is psychometrically sound and useful for practitioners working with diverse groups.